The Impact of Trusted Community Navigators in Improving Care Utilization Patterns for a Population With Chronic Kidney Disease Enrolled in Medicare Advantage: A Longitudinal Claims Based Study - Claude Pinnock; Francesca Gordon; Jordan Ziskin; Tom Carlough; Ken Wake (Journal of Primary Care & Community Health)
Background: Chronic Kidney disease (CKD) accounts for approximately 82 billion dollars of Medicare spend. Implementing culturally competent, community-based programs may be a strategy for changing utilization behaviors and lowering cost while maintaining quality in this population. Methods: A longitudinal claims based study was carried out from April 2023 to August 2024 in the state of CA to assess the impact of the program on cost, utilization, and quality metrics. A propensity matched approach was leveraged yielding of 203 pairs of CKD Medicare Advantage (MA) enrollees. A comparison of the difference of differences was performed between utilization, and available claims-based quality metrics. Results: Enrollees in the peer support program, Connect For Life (CFL) generated significantly lower costs of $461 pmpm (95% CI = −1037 to −10 037; P  = .016) significantly lower inpatient utilization of 172 per 1000 (95% CI = −10 to −330; P  = .037) and significantly higher outpatient utilization of 1212 per 1000 (95% CI = 90 to 2340; P  = .035). No differences were found in available quality metrics. Conclusions: For CKD MA enrollees in the intervention population, more efficient utilization patterns and lower costs while maintaining quality were observed. The tight propensity match left the study underpowered to detect significant changes for other care settings or individual stages of CKD.